Annelated P-containing heterocycles from aryl- and hetaryl-substituted phosphonium iodonium ylides with a methoxycarbonyl-group - Matveeva, Elena D.; Podrugina, Tatyana A.; Taranova, Marina A.; Melikhova, Ekaterina Yu.; Gleiter, Rolf; Zefirov, Nikolay S. (Tetrahedron, 2013)
Hetaryl-substituted phosphonium-iodonium ylides with a methoxycarbonyl group as acceptor proved to be highly reactive toward various alkynes in comparison with triphenyl-substituted analogue. We were able to isolate annelated P-containing heterocycles—λ5-phosphininothiophenes, λ5-phosphininofurans, λ5-phosphinolines, and rare polyaryl-substituted phosphonium salts, which can be traced back to three different rotamers of an intermediate adduct of the alkyne with the cation generated from the mixed ylide by removal of iodobenzene.
Gesehen am 29.06.2021